Comparative study of maxillary complete denture base retention using different impression materials (Mustansiria Dental Journal, 2018)
An impression taking for edentulous ridge is the first step in the fabrication of thecomplete denture prosthesis. Various theories have been proposed by differentauthors as how to achieve an optimum impression in different ways.The purpose of this study was to compare the retentive forces required to dislodgemaxillary complete denture bases fabricated by using different impression materials.Twenty completely edentulous patients were selected and three types ofimpression were made for each patient. The 1st group; final impression were madewith zinc oxide eugenol "ZOE", 2nd group; final impression were made with lightbody addition silicone impression material and 3rd group; final impression were madewith condensation impression material. Three stone casts were obtained for eachpatient and three denture bases were fabricated by short curing cycle, retention forceexamined and compared using strain gauge force transducer.Statistical analysis for the data collected using descriptive statistic, ANOVA andLSD, the result revealed that group A "Impression with ZOE" and B "Impression withaddition silicone" show nearly the same results while group C "impression withcondenation silicone" significantly less retentive force than that of group A and B.Retention of complete denture bases is greater in denture bases produced by zincoxide eugenole final impression material than the other examined final impressionmaterials.